Single‐Crystal Perovskite Solar Cells Exhibit Close to Half A Millimeter Electron‐Diffusion Length. Issue 47 (19th October 2022) - Turedi, Bekir; Lintangpradipto, Muhammad N.; Sandberg, Oskar J.; Yazmaciyan, Aren; Matt, Gebhard J.; Alsalloum, Abdullah Y.; Almasabi, Khulud; Sakhatskyi, Kostiantyn; Yakunin, Sergii; Zheng, Xiaopeng; Naphade, Rounak; Nematulloev, Saidkhodzha; et al.
Abstract: Single‐crystal halide perovskites exhibit photogenerated‐carriers of high mobility and long lifetime, making them excellent candidates for applications demanding thick semiconductors, such as ionizing radiation detectors, nuclear batteries, and concentrated photovoltaics. However, charge collection depreciates with increasing thickness; therefore, tens to hundreds of volts of external bias is required to extract charges from a thick perovskite layer, leading to a considerable amount of dark current and fast degradation of perovskite absorbers. However, extending the carrier‐diffusion length can mitigate many of the anticipated issues preventing the practical utilization of perovskites in the abovementioned applications. Here, single‐crystal perovskite solar cells that are up to 400 times thicker than state‐of‐the‐art perovskite polycrystalline films are fabricated, yet retain high charge‐collection efficiency in the absence of an external bias. Cells with thicknesses of 110, 214, and 290 µm display power conversion efficiencies (PCEs) of 20.0, 18.4, and 14.7%, respectively. The remarkable persistence of high PCEs, despite the increase in thickness, is a result of a long electron‐diffusion length in those cells, which was estimated, from the thickness‐dependent short‐circuit current, to be ≈0.45 mm under 1 sun illumination. These results pave the way for adapting perovskite devices to optoelectronic applications in which a thick active layer is essential. Abstract : Perovskite single crystals with thicknesses ranging from 20 to 300 µm can still exhibit efficient charge collection in the absence of an external voltage bias, resulting in high power conversion efficiency. The electron‐diffusion length in these crystals is calculated to be longer than 0.4 mm. This work demonstrates that perovskite crystals can offer more than what is currently expected.